The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1093/intimm/10.11.1703
|View full text |Cite
|
Sign up to set email alerts
|

Survival of long-lived plasma cells is independent of antigen [In Process Citation]

Abstract: Recent studies have shown that persistent specific antibody titer is provided by long-lived plasma cells (PC) which constitute a new kind of 'memory-providing cells'. In the present study, we examine the role of antigen for the long-term survival of PC and the maintenance of specific serum antibody titers. Using a novel cytometric technology, to identify and isolate antigen-specific PC, we analyzed long-lived PC of BALB/c mice, during their development (between day 1 and 10) after secondary immunization with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
274
1
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(296 citation statements)
references
References 72 publications
16
274
1
5
Order By: Relevance
“…The rapidly dividing CD38 ϩ ISCs presumably then acquire altered homing characteristics, resulting in their migration to sites including bone marrow (55,56), where they undergo terminal differentiation to yield long-lived quiescent CD38 ϩ plasma cells (38,45,52,53,57,58). In this way, Ig produced by the selected ISCs will be sustained for long periods even after Ag clearance (2,14). In contrast, the CD38 Ϫ ISCs, being CD40L dependent, will only survive and contribute Ig as long as Ag and T cell help are both available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapidly dividing CD38 ϩ ISCs presumably then acquire altered homing characteristics, resulting in their migration to sites including bone marrow (55,56), where they undergo terminal differentiation to yield long-lived quiescent CD38 ϩ plasma cells (38,45,52,53,57,58). In this way, Ig produced by the selected ISCs will be sustained for long periods even after Ag clearance (2,14). In contrast, the CD38 Ϫ ISCs, being CD40L dependent, will only survive and contribute Ig as long as Ag and T cell help are both available.…”
Section: Discussionmentioning
confidence: 99%
“…Activated memory cells rapidly proliferate and differentiate such that the memory lineage is preserved, whereas large numbers of plasma cells are concomitantly generated (1, 2, 6 -11). Thus, whereas plasma cells are mitotically quiescent and terminally differentiated, memory B cells are capable of consecutive phases of stimulation, expansion, selection, and generation of effector cells (7,8,(12)(13)(14). As a consequence, the population of memory B cells is maintained and even enhanced by frequent exposure to Ag (12,15), giving it the attributes of a "stem" type cell for the plasma cell lineage (16).…”
mentioning
confidence: 99%
“…From a personal point of view, we became interested in the lifestyle of memory lymphocytes when we started to analyze the persistence of plasma cells in the bone marrow 1, 2. Plasma cells had been identified as antibody‐secreting cells in 1947 3.…”
Section: Memory Plasma Cellsmentioning
confidence: 99%
“…The persistence of long‐lived plasma cells over long time periods qualifies them as true “memory” cells, memorizing the original antigenic challenge independent of continued antigenic stimulation,1 ie, maintaining information in the absence of the original instruction. We therefore suggest to designate them “memory plasma cells”, replacing the operational term “long‐lived” plasma cells used so far in the literature.…”
Section: Memory Plasma Cellsmentioning
confidence: 99%
“…The progenitor cells of anti-aGal nAb-producing B cells are thought to arise from B1-b cells in peritoneal and pleural cavities, and plasma cells mature in secondary lymphoid organ such as the spleen to produce anti-aGal Ab [25]. It has also been reported that long-lived memory and plasma B cells reside in the bone marrow [26]. Our data suggest that not only are there progenitor B cells but also long-lived plasma and memory B cells are tolerized by clonal destruction or anergy after treatment with aGal þ donor SC and CP.…”
Section: Discussionmentioning
confidence: 99%